Investigating the hepatitis B virus life cycle using engineered reporter hepatitis B viruses. Issue 1 (7th December 2017) - Nishitsuji, Hironori; Harada, Keisuke; Ujino, Saneyuki; Zhang, Jing; Kohara, Michinori; Sugiyama, Masaya; Mizokami, Masashi; Shimotohno, Kunitada
Abstract : Chronic infection with hepatitis B virus (HBV) increases the risk of developing fibrosis, cirrhosis or hepatocellular carcinoma. Current therapies are limited to type‐I interferons and/or nucleos(t)ide analogues; however, these are only partially effective. The development of novel anti‐HBV agents for new treatment strategies has been hampered by the lack of a suitable system that allows the in vitro replication of HBV. Studies of virus infection/replication at the molecular level using wild‐type HBV are labor‐intensive and time‐consuming. To overcome these problems, we previously constructed a recombinant reporter HBV bearing the NanoLuc gene and showed its usefulness in identifying factors that affect HBV proliferation. Because this system mimics the early stage of the HBV life cycle faithfully, we conducted a quantitative analysis of HBV infectivity to several human hepatocyte cell lines as well as the effect of dimethyl sulfoxide and HBV protein X on the early stage of HBV proliferation using this system. Furthermore, we developed a system to produce a reporter HBV expressing a pol gene. These reporter HBV may provide an opportunity to enhance our understanding of the HBV life cycle and aid strategies for the development of new anti‐HBV agents. Abstract : The newly developed reporter HBV provides good opportunity to explore new anti‐HBV agents as well as to analyze HBV life cycle.